Long-term effect of CFTR modulator therapy on airway nitric oxide. Issue 1 (9th January 2020) - Grasemann, Hartmut; Klingel, Michelle; Avolio, Julie; Prentice, Carley; Gonska, Tanja; Tullis, Elizabeth; Ratjen, Felix
The fraction of exhaled nitric oxide ( F eNO ) is generally lower in individuals with cystic fibrosis (CF), compared to healthy controls. Two recent studies reported that the cystic fibrosis transmembrane conductance regulator (CFTR) potentiator ivacaftor resulted in an increase in F eNO after 4 weeks' therapy [1, 2], suggesting that changes in F eNO have the potential to serve as biomarker of restored CFTR function. Ivacaftor results in a sustained increase in F eNO in children and adults with CF. The increase in F eNO may be related to changes in airway NO metabolism by myeloperoxidase. Lumacaftor–ivacaftor therapy does not have an immediate effect on F eNO . http://bit.ly/2mzqhds